DETECTION OF PUPPET'S MOTION USING MOTION CAPTURE APPLICATION WITH WEB CAMERA TO MOTION 3D DIGITAL CHARACTER - (NIM: 23207071), ISMAIL
The motion of characters in a 3D animation could be made by motion capture application. This motion capture application captures motion of full human bodies and maps it to motion of 3D characters. The capture of motion of full human bodies results in realistic characters' motion but the cost is relatively high. As an alternative, the motion capture application could capture the motion of part of human bodies or other things which are not part of human body. For example, Bottomi et al. in CoPuppet and Redei et al. in AVRATAR capture the motion of human fingers. In this thesis, a motion capture application was made to capture the motion of puppets. The puppets have markers with certain color and are motioned in front of web camera. Using color detection algorithm, the motion of the puppets is derived from the motion of the colored markers. In this color detection process, noise is eliminated by eroding and dilating processes. After collected, motion data are processed to determine the position and orientation of the puppets. The position and orientation of the puppets are further processed to motion a 3D digital character. In this thesis, performance of the application also being measured. The performance is measured by comparing the application frame rate and the camera frame rate. It is shown that the application frame rate is half the camera frame rate. Besides the application performance, also being measured range of color that could be captured by camera web. By detecting various colors, it is shown that light yellow is not detected by the camera web. To analyse the efficiency of the program, software profiling is performed. It is shown that processes use the most computation resources are dilating, eroding, and 3D model rendering process.